(untitled) (World Economics and Finance Bulletin, 2026)
This article comprehensively examines the theoretical and practical aspects of accounting for accounts payable in Uzbekistan in accordance with the requirements of International Financial Reporting Standard 9 (IFRS 9) "Financial Instruments". The study analyses the criteria for initial recognition of accounts payable as financial liabilities, subsequent measurement methods, the amortised cost model, and the specific features of applying the effective interest rate method. Particular attention is given to the derecognition of financial liabilities, their presentation in financial statements, and the challenges of harmonising national practice with international standards. Methodological problems encountered in measuring and accounting for accounts payable are identified through practical examples, and scientifically grounded proposals and recommendations for addressing them are developed. The findings obtained serve to enhance the transparency and reliability of financial reporting in enterprises, ensure greater accuracy in measuring financial liabilities, and improve accounting policies in conformity with international financial reporting standards